Rotala dhaneshiana, a new species of Lythraceae from India - K, Ratheesh Narayanan M; N, Sunil C; T, Shaju; K, Nandakumar M; M, Sivadasan; Alfarhan, Ahmed H (Phytotaxa, 2014)
Rotala dhaneshiana, a new species of Lythraceae collected from a semi-marshy area of Wayanad Wildlife Sanctuary in Kerala, India is described and illustrated. It is closely allied to R. malampuzhensis usually in having trimerous flowers, but differs in having 4-angled, narrowly winged stems, long epicalyx lobes alternating with sepals, obovate-apiculate petals, and absence of nectar scales. It resembles R. juniperina, an African species in having trimerous flowers but differs in having sessile, decurrent-based leaves and sessile pistil.